Epidemiology of firework injuries Chahar Shanbeh Soori eve ceremony, in Iran - Aghaee, Abbas; Rezaee, Sattar; Haddadi, Mastaneh; Eini, Elaheh (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Many people sustain injuries in Chahar Shanbeh Soori ceremony that is held at the final hours of the last Tuesday of every year. This study aimed to identify epidemiology of injuries that caused in this ceremony in 2009. Materials and Methods: At this epidemical descriptive study, data and specifications of people, injured in Chahar Shanbeh Soori ceremony, were collected by universities of medical sciences using standard and specified questionnaires and then sent to Preventive of Accident and Emergency Medicine Department to be evaluated. Demographic and epidemic information, as epidemic areas, states, type of explosive materials and jobs of injured people were studied. At the end, data were compared with information of a few years ago. Results: On the whole, 1817 people were injured in this ceremony (%83.2 male and 16.8 female), and average age of them was 20.9 ± 10 years old. Subgroup of 15-24 years old, are the most injured people and the most injuries, were caused by inflammable materials. More than one third of injuries of organs are related to hands (%34.4). %81.4 of injured people, were outpatients, and the rest were hospitalized. Conclusion: as the most group of injured people, were students injured during game with inflammable materials, warning programs, should presented to parents via media and schools. Keywords : Injury, Damage, ceremony, burn, gaming with fire, Chahar Shanbe Soori, inflammable materials REFERENCES -American Academy of Pediatrics (2001). Committee on Injury and Poison Prevention. Fireworks- related injuries to children. Pediatrics . 108 (1) 190–191. -Fogarty BJ Gordon DJ (1999). Firework related injury and legislation: The epidemiology of firework injuries and the effect of legislation in Northern Ireland. Burns. 25 (1) 53-56 -Isa AR Moe H (1991). Fireworks related injuries during Hari Raya festival in Hospital University Sains Malaysia 1986 to 1990. The Medical Journal of Malaysia. 46 (4) 333–7. -Jing Y Yi-qiao X Yan-ning Y and et al (2010). Clinical analysis of firework-related ocular injuries during Spring Festival 2009. Graefes Arch Clin Exp Ophthalmol. 248 (3) 333–338. -Mansouri MR Mohammadi SF Hatef E and et al (2007). The Persian Wednesday Eve Festival ‘‘Charshanbe-Soori’’ M reworks eye injuries: a case series. Ophthalmic Epidemiology. 14 (1) 17–24. -Mohammad M Al-Qattan, Al-Tamimi A.S (2009). Localized hand burns with or without concurrent blast injuries from M reworks. Burns. 35 (3) 425–429. - Newell FW Vail D (1972). Fireworks blindness. Am J Ophthalmol. 74 (1) 167–168. -Puri V Mahendru S Rana Rand et al (2009). Firework injuries: A ten-year study. Journal of Plastic, Reconstructive Aesthic Surgery. 62 (9) 1103–11. -Saadat S Naseripour M Smith GA (2010). The health and economic impact of M reworks-related injuries in Iran: A household survey following the New Year’s Festival in Tehran. Injury. 41 (7) 28-33. -See LC Lo SK (1994). Epidemiology of M reworks injuries: The National Electronic Injury Surveillance System, 1980– 1989. Annals of Emergency Medicine. 24 (1) 46–50. -Sheller J Muchardt O Jonsson Band et al (1995). Burn injuries caused by M reworks: effect of prophylaxis. Burns. 21 (1) 50–3. -Tavakoli H and et al (2011). Firework-related Injuries in Tehran’s Persian Wednesday Eve festival (CHAHARSHANBE SOORI). The Journal of Emergency Medicine. 40 (3) 340-5 -Vassilia K Eleni P Dimitrios T (2004). Firework-related childhood injuries in Greece: a national problem. Burns. 30 (2) 151–153. -Zohar Z Waksman I Stolero J et al (2004). Injury from Mreworks and M recrackers during holidays [Hebrew]. Harefuah. 143 (10) 698–701.